DIFFERENT METHODOLOGICAL APPROACHES REGARDING MEASUREMENT OF RULE OF LAW (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
In this paper, we aim to present the major challenges in the attempt to quantify the concept of rule of law. At the present, there are several approaches for measurement of rule of law among different countries among time. This paper analyses four different indicators that are frequently used, including: (1) Rule of Law index, published by the World bank in the Worldwide Governance Indicators database; (2) Rule of Law index published by the World Justice Project; (3) Rule of Law set of indicators, including property rights, judicial effectiveness and government integrity, published by the Heritage Foundation in the Index of Economic freedom; and (4) Rule of Law indicator integrated in the Civil Liberties report prepared and published by Freedom House. We focus on the Western Balkan countries, by using case studies and situation analysis. Assuring rule of law is one of the basic preconditions for EU integration of this region.